DESIGN AND ANALYSIS OF GAS-COOLED FAST REACTOR USING MODIFIED CANDLE BURNUP SCHEME IN RADIAL DIRECTION - Handayani Irka, Feriska
The subject of non-proliferasion has always been at the forefront of nuclear reactor manufacturing. Natural uranium, which contains small quantities of the U-235 isotope, must be enriched beforehand it can be utilized in the reactor under critical conditions. Apart from being sensitive to proliferasion risks, uranium enrichment necessitates additional costs in its production. Natural uranium can be utilized directly in commercial reactor cores without enrichment, but only with certain strategic procedures. Theoretical studies on the utilization of fuel from the conversion of U-238 to Pu-239 and the use of uranium waste have been conducted since 1958. This is known as a breed and burn reactor (B&B reactor) or a travelling wave reactor. Sekimoto developed a similar burner model called CANDLE (Constant Axial Shape of Neutron Flux, Nuclide Densities, and Power Shape During Life of Energy Production), and Su’ud made small modifications to this burning scheme and called it Modified CANDLE. After the startup reactor operated we just need a natural uranium as fuel cycle input to keep the reactor critical during the burn-up period of time. To achieve the gas-cooled fast reactor design, parameter surveys in the form of selecting reactor core geometry, cladding materials, and fuel materials are required. SRAC (Standard Reactor Analysis Code System) programming with JENDL (Japanese Evaluated Nuclear Data Library) 4.0 library data was used to calculate reactor criticality and fuel cell performance. Data from parameter surveys are neutronically investigated and adjusted in order to create a reactor designed for maintaining criticality for ten years without refueling, with excess reactivity of less than 1% ?k/k and a Power Peaking Factor (PPF) of less than two at the end of cycle (EOC). According to the results of the parameter study, the pancake reactor type with a diameter of 220 cm and a height of 165 cm produces a relatively small neutron leakage when compared to the balanced core type and the tall core type. Because of its neutron economy, radiation resistance, high melting point, and high thermal conductivity, silicon carbide (SiC) was chosen as a cladding material in this study. Nitride fuel with 99% N-15 enrichment has advantages from the neutronic and thermal-hydraulic side of the reactor. Optimisation of the design parameter survey results revealed that the fuel fraction can be reduced to 62%. Next, the output power was increased to 475 MWTh, an increase of 18,75% over the initial design of 400 MWTh. Optimization was performed to minimize the active core height, with optimal results obtained at a height of 163 cm. Finally an optimal reactor design that complied with the research objectives was obtained: a pancake-type reactor with a diameter of 220 cm and a core height of 163 cm, SiC cladding, nitride fuel with a fuel fraction of 62%, and a reactor output power 475 MWTh. The result show maximum burn-up level of 38,7 %HM and maximum conversion ratio about 15 and minimum about 1,2. The average power level at BOC, MOC and EOC are 77,46 W/cc, 79,29 W/cc, and 81,12 W/cc respectively.